2005
DOI: 10.1042/bst0330173
|View full text |Cite
|
Sign up to set email alerts
|

Microbial reduction of selenate and nitrate: common themes and variations

Abstract: A number of biochemically distinct systems have been characterized for the microbial reduction of the oxyanions, selenate (SeO(4)(2-)) and nitrate (NO(3)(-)). Two classes of molybdenum-dependent nitrate reductase catalyse the respiratory-linked reduction of nitrate (NO(3)(-)) to nitrite (NO(2)(-)). The main respiratory nitrate reductase (NAR) is membrane-anchored, with its active site facing the cytoplasmic compartment. The other enzyme (NAP) is water-soluble and located in the periplasm. In recent years, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Previous studies of whole cells of E. cloacae SLD1a-1 have suggested that the membrane-bound nitrate reductase is not involved in the process of selenate reduction (31). To test this hypothesis, the nitrate reductase was purified and assayed for selenate reductase activity in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of whole cells of E. cloacae SLD1a-1 have suggested that the membrane-bound nitrate reductase is not involved in the process of selenate reduction (31). To test this hypothesis, the nitrate reductase was purified and assayed for selenate reductase activity in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, both NarG and NarZ in membrane fractions from Escherichia coli have been reported to show selenate reductase activity, but only when assayed in the presence of excess (160 mM) sodium selenate (1). Clearly, it is evident that membrane-bound nitrate reductases are poor reducers of selenate (1,31) and may not contribute significantly to global selenate reduction, particularly in areas enriched with both selenate and nitrate. Consequently, novel enzyme systems that selectively catalyze the reduction of selenate have been sought (2,26,32), and to date, detailed biochemical studies have been limited mainly to a single species, Thauera selenatis (7,17,19,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The specific activities for selenate reduction by nitrate reductases are, however, 15 to 518 times lower (Watts et al 2005) and the affinity constants (K M ) 2.3 times higher for selenate compared to nitrate reduction (Sabaty et al 2001). Consequently, selenate is reduced by these enzymatic systems at low nitrate concentrations only .…”
Section: Introductionmentioning
confidence: 98%
“…In addition to this chemical reduction, enzymatic processes have also been described. The reduction of oxyanions has often been associated with denitrification, since bacterial nitrate reductases have been shown to catalyze selenate reduction (24,40). However, T. selenatis and E. cloacae SLD1a-1 possess a specific selenate reductase (4,39).…”
mentioning
confidence: 99%